02.03 Influence of free fatty acids on osteoblasts and osteoclasts in rheumatic diseases. (1st March 2017) - Frommer, Klaus; Schäffler, Andreas; Lange, Uwe; Rehart, Stefan; Steinmeyer, Jürgen; Rickert, Markus; Müller-Ladner, Ulf; Neumann, Elena
Abstract : Background: Increased amounts of visceral fat are often associated with lower bone density. Also, in obese patients an increased risk of osteoarthritis can be seen in non-weight bearing joints. Chronically elevated free fatty acid (FFA) levels as occurring in obesity may therefore also play a role in bone loss. We hence analysed if and how FFA influence cells of bone metabolism in rheumatic diseases. Methods: Primary osteoblasts (OB) were isolated from cancellous bone of OA and RA patients undergoing knee joint surgery. Osteoclasts (OC) were differentiated from peripheral blood mononuclear cells (PBMC). OB and OC were stimulated with the saturated FFA palmitic acid (PA) and the unsaturated FFA linoleic acid (LA). Protein secretion was quantified by immunoassays, mRNA expression by real-time PCR. Mineralization activity was quantified using Alizarin Red S staining, differentiated OC were quantified by counting TRAP-positive multinuclear cells. Toll-like receptor (TLR) 4 and TLR2 were blocked by neutralising antibodies. Results: Stimulation with PA or LA increased OB secretion of the proinflammatory cytokine IL6 (up to 9-fold ↑) and the chemokines IL-8 (up to 221-fold ↑), GRO-α (from below detection level to detectable levels) and MCP1 (up to 16-fold ↑). RANKL and OPG were not influenced by FFA on protein and mRNA level. In osteoblasts, activity (ALP/collagen type I) and differentiation markers (e.g. osteocalcin) as well as production of inorganic matrix were not altered by FFA stimulation. TLR4 but not TLR2 blockade significantly reduced PA-induced IL-8 secretion by OB. Secretion of IL-8 by RA OC was increased by FFA, while MMP-9 was reduced. The mRNA expression of osteoclast activity markers (CLCN7, CTSK, TCIRG) remained unchanged. However, the number of TRAP positive multinuclear cells formed from RA PBMC was decreased (by around 50%). Conclusions: The pro-inflammatory effect of certain FFA on osteoblasts and osteoclasts may indirectly contribute to bone loss, while the reduction of mature OC after FFA stimulation suggests an inhibitory effect on bone resorption. In osteoblasts, FFA signalling is at least in part mediated by TLR4, but not by TLR2.